Genetic linkage of β and γ subunits of epithelial sodium channel to systolic blood pressure - Wong, Zilla YH; Stebbing, Margaret; Ellis, Justine A; Lamantia, Angela; Harrap, Stephen B (The Lancet (British edition), 1999)
Mutations in the genes on chromosome 16p12 that encode the β and γ subunits of the epithelial sodium channel ( SCNNIB and SCNNIG, respectively) have been linked with rare sodium-dependent forms of low and high blood pressure. Other DNA variants in or around these genes may contribute to variation in blood pressure and the risk of coronary heart disease and stroke. We studied 286 white families from the general population in Victoria, Australia. Each family comprised both parents and two natural children. All participants were genotyped at chromosome 16p12 by use of four highly polymorphic microsatellite markers. Quantitative phenotype measurements were correlated with genotype in identity-by-descent sibling-pair linkage analyses. We found significant linkage between systolic blood pressure and chromosome 16p12 after parametric analyses (p=0·0003) and non-parametric analyses (p=0·001). The mean difference in systolic blood pressure between siblings identical-by-descent at these loci was half as large (7·1 mm Hg) as the difference between siblings non-identical at these loci (14·0 mm Hg, p=0·001). No linkage between chromosome 16p12 and diastolic blood pressure or body-mass index was observed. Chromosome 16p12 and the SCNNIB and SCNNIG genes are implicated in the physiological variation of systolic blood pressure. Our findings are important in explaining individual cardiovascular risk within the general population.